Urrets-Zavalia syndrome following goniotomy in a child - Chelnis, James G.; Sieminski, Sandra F.; Reynolds, James D. (Journal of AAPOS, 2012)
Urrets-Zavalia syndrome is a surgical complication in which the pupil remains fixed and dilated after a procedure. It is believed to be caused by brief periods of high intraocular pressure. Although the syndrome was originally associated with penetrating keratoplasty, it has subsequently been associated with other procedures. We report the case of a 13-year-old boy with congenital glaucoma who developed Urrets-Zavalia syndrome after goniotomy. After 2 years of follow-up, the pupil remained fixed and dilated in that eye. To our knowledge this is the first case of Urrets-Zavalia syndrome to be reported following goniotomy and the first to occur in a child.